If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5 + 3x) = 7 + 6x (5 * 2 + 3x * 2) = 7 + 6x (10 + 6x) = 7 + 6x Add '-6x' to each side of the equation. 10 + 6x + -6x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 10 + 0 = 7 + 6x + -6x 10 = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 10 = 7 + 0 10 = 7 Solving 10 = 7 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -2(h+3)=-5(h-6) | | n^4-126=0 | | X^2/y/w/2y | | 2(1+5x)=2+5x | | -9=u+6 | | 12+4*x=24 | | (3c/9)=4-c | | 10x-5+35=13x+3 | | 14x^2/49x^3 | | 3/4-3/6= | | (3y/5)=3y-4 | | x+3+7=2x-10-x | | 7x-8y=29 | | 12y=18*24 | | x(x+2)(x+3)(x+5)-72= | | 2(x-4)2=48 | | 9.5b-2.5-8b=-17.5 | | y=22-5x | | 9-8v=-6v-9 | | 10f=3f+7 | | 3*x-16=7 | | 8E-9= | | logb(x)+logb(x+3)=logb(28) | | 4n-2(n-6)=-16 | | (4+4b)+(1+5c)= | | 1-7*x=6 | | 9y=7y+16 | | 5+5+x+x=24 | | v*6p=14 | | -3r=-4r-8 | | -1-7*x=6 | | 3x=888-x |